ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH ON CONSUMER DECISION MAKING TO STAY IN STAR RATING HOTEL IN MANADO CITY - Mokodaser, Andreas; Lapian, S.L.H.V. Joyce (Universitas Sam Ratulangi, 2015)
Hotel has became the new business that developing quickly in Manado. It is happened due to the Manado tourism city program established by the city government which indirectly opening up the opportunities for the growth of hospitality industry in Manado. The purpose of this study is to analyze the criteria hotel that influence consumer and analyze the most star rating hotel chosen by the people. This research held from May until June 2015 in Manado city. The respondent are 30 person with using purposive sampling technique to determine the respondent. The respondent must have an experience at least spend one night in three star rating hotel (Peninsula, Arya Duta, Novotel). The method used is Analytical Hierarchy Process (AHP) to compare each star rating hotel as the alternatives on each criteria developed based on the star rating hotel criteria and score it by using preference scale. As the result, there are two from four criteria that influence the consumer to choose star rating hotel. Price is the most preferred criteria followed by location in second position. In best hotel result, Peninsula become the best hotel chose by respondent, followed by Arya Duta and Novotel. The star rating hotel management hotel should consider about establish the price adjusted to the location and give the best service to consumer. Keywords : analytical hierarchy process, consumer purchase decision